Low Dose Antigen Exposure for a Finite Period in Newborn Rats Prevents Induction of Mucosal Tolerance - Buchanan, Rachelle M. (Public Library of Science, 2012)
BACKGROUND: In adult rats, initial exposure to antigens by a mucosal route triggers tolerance such that any subsequent re-exposure, even by a systemic route, results in suppression of immunity. The newborn’s gut is semi-permeable for a finite period to allow maternal antibodies to enter the newborn’s circulation. We propose that antigens introduced in extreme early life can readily traverse the gut wall and therefore circumvent induction of mucosal tolerance. METHODOLOGY/PRINCIPLE FINDINGS: Rat pups were gavaged with low-doses of ovalbumin (OVA; oral exposure group) or saline (parenteral control group) every second day for several weeks followed by an intraperitoneal (i.p.) injection at 1 month of age. When gavage was initiated the day after birth, newborn oral exposure pups responded with significantly higher anti-OVA IgA, IgM, IgG2a, and IgG1 titres in their serum and anti-OVA IgA, IgG2a and IgG1 titres in their lungs compared to negative control pups. Oral exposure alone failed to induce immunity. Pups exposed to the same treatment regimen starting at 14 days of age showed induction of mucosal tolerance after i.p. immunization. Newborn oral exposure groups subjected to secondary i.p. immunization responded with significantly increased humoral immunity in lung and sera suggesting that once antigen-specific mucosal tolerance if circumvented, it persists. Lymphocytes derived from mesenteric lymph node cells re-simulated with OVA ex vivo, from newborn oral exposure pups exposed to secondary immunization produced significantly higher IFN-γ expression and lymphocyte proliferation relative to control pups indicating prevention of tolerance in the cell-mediated immune system. CONCLUSIONS/SIGNIFICANCE: This work demonstrates that newborns may be uniquely qualified to prevent induction of mucosal tolerance to oral antigens. These results should be further explored to establish whether prevention of tolerance by early life oral vaccination can be exploited to prime for mucosal as well as systemic immunity and thus protect this susceptible population against infectious diseases.